Ecological aspects of preservation of valuable components of plant raw materials in the production of non-alcoholic beverages - Golovanova , Ya.A.; Romanova, Zoriana; Kosoholova, Liudmyla (Problems of Environmental Biotechnology, 2021)
The nutritional value of plant raw materials is determined by the content of vitamins, minerals, polyphenols and other important components. It is important to preserve valuable components in the processing of raw materials for the production of beverages. It is proposed to revive and improve the recipes of fruit drinks.